O imaginário social através da mídia: uma perspectiva discursiva da construção identitária do professor - Nascimento, Carla Correia de Almeida do (2024)
The discourse is permeated by imaginary formations that function in discursive processes, representing the social and ideological places of the subject. Under this premise, this work proposes the discursive study of the imaginary constructed about the teacher by the media, through educational institutions, analyzing the representations that are perpetuated in society and (re)create their identity. Using the theoretical-methodological device of Pecheutian Discourse Analysis, based on Michel Pêcheux (1993; 1994; 1995; 2015), and Orlandi (2005; 2007; 2011; 2012), in a dialogue with Cultural Studies, supported by Stuart Hall (2001), Zygmunt Bauman (2005), and Claude Dubar (1997; 2009) that address issues related to the concept of identity, identity construction, a parallel will be drawn between the concepts of imaginary representations and identity construction. The study also includes contributions from social psychology, especially the concepts of identity by Antônio Carlos Ciampa (1987; 1989; 2002), by Serge Moscovici (1961, 1978, 2005, 2007), in addition to other texts that deal with this theme. The general objective is to investigate the meanings that are (re)produced in the media about teachers, through educational institutions, and formulate the representations that are perpetuated in society. The central question is: What meanings are produced and permeate the discursiveizations of contemporary statements, formulating the images and social representations about teachers in the media, on educational institution websites, and how do these images (re)create the teacher's identity? Consequently, this study provides a reflection on the symbolic and power relations that constitute discursive formations and that are established as truth in the position of the teacher subject, enabling a shift in the perspective of this subject, the teacher, as well as in the social perspective in relation to this theme.